2007
DOI: 10.1111/j.1365-2672.2007.03331.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of rayon swab surface sample collection method forBacillusspores from nonporous surfaces

Abstract: Aim:  To evaluate US Centers for Disease Control and Prevention recommended swab surface sample collection method for recovery efficiency and limit of detection for powdered Bacillus spores from nonporous surfaces. Methods and Results:  Stainless steel and painted wallboard surface coupons were seeded with dry aerosolized Bacillus atrophaeus spores and surface concentrations determined. The observed mean rayon swab recovery efficiency from stainless steel was 0·41 with a standard deviation (SD) of ±0·17 and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 13 publications
1
49
0
1
Order By: Relevance
“…The spore surface concentrations are controlled by varying settling time and the initial aerosolized spore concentration in the chamber. Brown et al (4)(5)(6) tested various methods of collecting samples of Bacillus subtilis spores on porous and nonporous surfaces using this approach. In these studies, surface spore concentrations of 10 2 to 10 5 CFU/cm 2 were achieved.…”
mentioning
confidence: 99%
“…The spore surface concentrations are controlled by varying settling time and the initial aerosolized spore concentration in the chamber. Brown et al (4)(5)(6) tested various methods of collecting samples of Bacillus subtilis spores on porous and nonporous surfaces using this approach. In these studies, surface spore concentrations of 10 2 to 10 5 CFU/cm 2 were achieved.…”
mentioning
confidence: 99%
“…Further, because of the variability produced by having to deal with live organisms, it is not likely that the accuracy in measurement for spores will meet the NIOSH criteria. In studies of spore recovery from surfaces, the variability of CFUs per sample is not usually reported, only the recovery efficiency and its variability (Rose et al 2004;Hodges et al 2006;Brown et al 2007a;2007b;2007c). Recovery efficiency values reported in the Brown et al studies had a range of 28-90%; .…”
Section: Introductionmentioning
confidence: 99%
“…The spores were allowed to settle onto flooring material placed on a bench. Brown et al (2007a;2007b;2007c) spores into a chamber and produced surface concentrations in the range of 10 2 to 10 5 colony forming units per cm 2 . In the anthrax attack of 2001, some of the material was believed to be in a "fluidized" form (defined here as having fumed silica added).…”
Section: Introductionmentioning
confidence: 99%
“…The tested deposition with aluminum oxide particles, monodisperse polystyrene spheres, and oleic acid droplets; however, they ultimately concluded that biological particle tests are needed due to the additional complications they add to the tests. Brown et al, aerosolized BG spores into a chamber and produced surface concentrations in the range of 10 2 to 10 5 colony forming units per square centimeter for the purposes of swipe sampling (Brown et al, 2007a(Brown et al, , 2007b(Brown et al, , 2007c. The chamber included a cylinder mixing chamber, constructed from carbon steel with enamel-coated surface, and a diameter of 45 cm, a height of 30 cm, and a total volume of 0.048 m 3 .…”
Section: Aerosol Test Chambersmentioning
confidence: 99%
“…A better choice is the rayon or macrofoam (Probst et al, 2010). Different studies have shown different removal efficiencies for the spores: vacuum filter sock sampler-28.2% (Brown et al, 2007c); nylon-flocked swabs-41.6% (Brown et al 2007c), and BiSKit have had efficiencies up to 47.3% (Buttner et al, 2004). Despite the increase in studies, there is still an overall lack of consensus for spore removal in the literature (Probst et al, 2010).…”
mentioning
confidence: 99%